Pluralism and Multiculturalism: an Islamic Perspective (American Journal of Islam and Society, 2001)
This article attempts to reconceptualize the theories of pluralism,ethnicity and multiculturalism by analyzing the present predicament ofMuslims and their mode of organization. However, this cannot be donein isolation from the normative theory, which is grounded in the Islamicsources and worldview. It provides an analytical insight into the interfaceof unity and diversity and limitation of achieving a haixnoniousrelationship between them in the modem western societies. Ideals of thewestem social theory are critiqued through the Islamic ideals toconceptualize alternative way of socio-political organization.